DEFINING AND ACCOUNTING FOR DEPRECIATION. - Scott, D. R. (The Accounting Review, 1945)
The article presents information on accounting for depreciation. Depreciation may be defined as an accounting cost which is arrived at by the use of methods which do not "attempt to measure the exhaustion which actually takes place within a given period," we thereby divorce the depreciation problem from the everyday world of business experience in which managerial decisions are made. Unquestionably, managements in their selection of depreciation methods have sometimes had purposes in mind other than an accurate accounting for depreciation. They have sometimes been motivated by an undue regard for financial conservatism. Even aside from the selection of methods, their depreciation policies have sometimes brought accounting results which have been positive misrepresentations of the facts. However, the accounting profession cannot afford to countenance such practices and still less can accountants afford to make them a basis for their own analysis of the problem of depreciation. The fact that managements have used methods of depreciation with different ends in view does not mean that the different methods rest upon basically different assumptions.